Cooking myths : fire the imagination along with the stove - Tsappa, Lilian (My University, 2021)
What if food became the medium and the end-result, as nourishing and enticing to the ear as to the palate? Inviting conversation and interaction, so that at the end of the day, on the weekend or a special occasion, we come together — in the kitchen or online — to prepare a meal and talk about it? Food for thought is the popular term, and the stories that accompany this collection of family recipes from Greece and Cyprus, meat-based and vegetarian, promise savory tastes of classical mythology, history, philosophy, art, geography, and science (with a dash of artistic license). Each selection centers on a basic food: egg, lemon, olive, wine, grains and legumes, milk, fruit, and fish; each alluding to a story from ancient Greece. Tales of temperamental gods mingling in the lives of mortals, heroes fighting monsters, stories of life and death, love and war, adventures and ideals; and beyond the particulars of each story, layer upon layer of symbolism and insight about a human’s relation to human, to nature, to God, and to the cosmos. And we realize, perhaps, that the same elements, relations and principles that make up a good story are also essential for a good recipe, and for a well-lived life: authenticity, balance, consistency, and more. Select a recipe and embark on a journey of discovery. Cooking Myths promises to fire your imagination along with your stove!